Stages of development of the Middle-Late Devonian ICHTHYOFAUNA (Placodermi: Antiarchi) from the northern Eurasia - S. V. Moloshnikov (Известия высших учебных заведений: Геология и разведка)
Three stages, namely Middle Devonian (I), Early Late Devonian (II) and Late Late Devonian (III), are distin-guished in the evolution of antiarchs (Placodermi, Antiarchi) in the Middle-Late Devonian of Northern Eurasia. These stages are set by changing the systematic composition, appearance and extinctions of antiarch taxons, as well as the dominance of different antiarch groups in the ichthyocomplexes. The first stage is of Eifelian and Givetian in age and characterized by the development mainly of the asterolepiform antiarchs of the families Pterichthyodidae and Asterolepididae, as also by the primitive bothriolepiform Dianolepididae. Rare bothriolepidids were present in some regions of Northern Eurasia. The second (Frasnian) stage is marked by the bothriolepidid increasing in numbers. The bothriolepidids became widely spread in Northern Eurasia. The third stage is of Famennian in age and described mainly by the bothriolepiforms from the families Bothriolepididae and Tubalepididae. Rare remigolepids were present among asterolepiforms during this stage. The characteristic of the stages is given, and position of their borders is discussed. The most significant changes in taxonomic composition of the antiarch fauna in the Northern Eurasia occurred at (or near) the borders of Givetian and Frasnian, Frasnian and Famennian ages.